Chiral Pseudo-D6h Dy(III) Single-Molecule Magnet Based on a Hexaaza Macrocycle - Jia-Hui Liu; Yi-Shu Jin; Jinkui Tang; Cai-Ming Liu; Yi-Quan Zhang; Hui-Zhong Kou (Molecules)
A mononuclear complex [Dy(phenN6)(HL′)2]PF6·CH2Cl2 (H2L′ = R/S-1,1′-binaphthyl-2,2′-diphenol) with local D6h symmetry was synthesized. Structural determination shows that Dy3+ was encapsulated within the coordination cavity of the neutral hexaaza macrocyclic ligand phenN6, forming a non-planar coordination environment. The axial positions are occupied by two phenoxy groups of binaphthol in the trans form. The local geometry of Dy3+ closely resembles a regular hexagonal bipyramid D6h configuration. The axial Dy-Ophenoxy distances are 2.189(5) and 2.145(5) Å, respectively, while the Dy-N bond lengths in the equatorial plane are in the range of 2.524(7)–2.717(5) Å. The axial Ophthalmoxy-Dy-Ophthalmoxy bond angle is 162.91(17)°, which deviates from the ideal linearity. Under the excitation at 320 nm, the complex exhibits a characteristic emission peak at 360 nm, corresponding to the naphthalene ring. The AC susceptibility measurements under an applied DC field of 1800 Oe show distinct temperature-dependent and frequency-dependent AC magnetic susceptibility, typical of single-molecule magnetic behavior. The Cole–Cole plot in the temperature range of 6.0–28.0 K was fitted using a model incorporating Orbach and Raman relaxation mechanisms, giving an effective energy barrier of Ueff = 300.2 K. Theoretical calculations on complex 1 reveal that the magnetization relaxation proceeds through the first excited Kramers doublets with a calculated magnetization blocking barrier of 404.1 cm−1 (581.4 K).